The middle blocker in volleyball: A systematic review - Millán-Sánchez, A.; Morante Rábago, J. C.; Ureña Espa, A. (Journal of Human Sport & Exercise, 2019)
The objectives of this systematic review were to verify the existing scientific literature published in electronic databases about middle players in volleyball, and to describe a profile middle players should fulfill in order to achieve the highest possible level. The PRISMA protocol was followed. A search of the literature was carried out in electronic databases (ISI Web of Science™, Scopus and SPORTDiscus). Of the 1266 initial results, 41 articles were selected, comprised between 2003 and 2016. The main topics studied about middle blockers are: match analysis, technique, physical effort, muscle strength, injuries, body measures and mental skills. Overall, middle blockers tend to be the tallest and heaviest players with an ectomorph somatotype, and present the largest reach when jumping. Blocking and attacking (i.e. first tempo attack) are their main functions, thus they should dominate them. They present a higher risk of injury, particularly in their knees and fingers. Mentally, they seem to show less toughness and resiliency than other playing positions.